Library websites popularity: does Facebook really matter? - Mohd Zain, Wahidah; Othman, Roslina (2014)
The purpose of this paper is to determine whether the utilization of social media (Facebook) is an important factor in increasing the visibility of the library site usage in Malaysian public universities. Nine top ranked Malaysian public universities involved in this research and number of Facebook followers for each library website is listed. Alexa software was used as the approach to study the issue of visibility. Alexa is able to determine web site usage, by showing the percentage of visitors of library related subdomain(s) as listed in the top subdomains for each University website (domain) over a month. It is found that Universiti Utara Malaysia library website scored the highest percentage of visitors based on the library related subdomain(s) as listed in the top subdomains for the University website in Alexa. To check such irregularities in access, this paper use EvalAccess 2.0 and it is found that Universiti Sains Malaysia’s library website scored higher irregularities. In term of number of Facebook followers, Univesity of Malaya library has the highest score. It is showed that the utilization of social media (Facebook) is not yet an important factor in increasing the visibility of the library websites. However, expectedly, top ranked universities’ library web sites, are more visible and popular. This research is limited to the situation in Malaysia where public universities are more noticeable and seldom face financial constraints rather than private universities. It is highly important for those universities’ library web sites that are not highly visible to initiate the necessary measures in improving the development of their web sites as the usage of the website is an indicator of online quality.